The Reproductive Biology of Shortfin Scad (Decapterus macrosoma) In Banda Sea Landed at TPI Sodoha, Kendari Southeast Sulawesi: Biologi reproduksi layang deles (Decapterus macrosoma) di Laut Banda yang didaratkan di TPI Sodoha, Kendari Sulawesi Tenggara) - Irma; Hamid, Abdul; Nadia, La Ode Abdul Rajab (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, IPB University, 2025)
This study aims to determined of the reproductive biology of the shortfin scad (Decapterus macrosoma) including sex ratio, gonad maturity level, gonad maturity index, fecundity, and size at first sexual maturity. This study was carried out from January to February 2025 at the fish auction place (TPI) Sodoha, Kendari. Fish samples were obtained from catches in the western Banda Sea using mini purse seines and landed at the Sodoha TPI, Kendari. Samples were separated by sex, then measured for length using a ruler with an accuracy of 0,5 mm and then measured for fish weight with a digital scale with an accuracy of 0.01 grams. Observation of the gonad maturity level was carried out by morphological and determination of fecundity using the gravimetric method. The results of the male and female sex ratio study showed an unbalanced, that is male of 105 individuals and female of 52 individuals. The level of male and female gonad maturity was dominated by the immature gonad category, and the male gonad maturity index ranged from 0.0830-2.5847% and the female ranged from 0.0971-2.4535 %. The first sexual maturity size of male and female shortfin scad were 232 mm and 224 mm, respectively, with fecundity ranging from 15,495 to 544,110 eggs.